Simulasi Dampak Liberalisasi Perdagangan Bilateral RI-China terhadap Perekonomian Indonesia: Sebuah Pendekatan SMART Model - Sabaruddin, Sulthon Sjahril (Jurnal Ekonomi Kuantitatif Terapan, 2013)
This paper attempts to evaluate the impact of trade liberalization between Indonesia and China to the Indonesian economy. In order to evaluate the impact on the Indonesian economy,the study uses a method of model analysis so-called Software for Market Analysis and Restrictions on Trade (SMART). The implications of the impact RI-China trade liberalization analysis in 2009 with a complete tariff dismantlement are the welfare of the Indonesian society, by utilizing the analysis of change in Consumer Surplus and a decrease in Deadweighted Loss. The paperconcludes that trade liberalization RI-China with zero tariffs results in a positive impact on the welfare of the Indonesian society.
Keywords: free trade; trade liberalisation; partial equilibrium analysis; Software for Market Analysis and Restrictions on Trade Model (SMART)